A Strength-Based Framework for Realizing Latino Young Children's Potential. (October 2021) - Gennetian, Lisa A.; Cabrera, Natasha; Crosby, Danielle; Guzman, Lina; Smith, Julia Mendez; Wildsmith, Elizabeth
Hispanic children experience poverty at rates two to three times higher than white children. Latino households with children, in general, have high parental employment coupled with low levels of parental education and stagnant parental earnings relative to non-Latino peers. While many Latino children live in neighborhoods that do not have access to high-quality early education, Latino children, on average, are raised in a home environment that offers economic stability and security, the presence of two parents, and socially supported family and community networks. Furthermore, though Hispanic children's school achievement outcomes lag behind those of their peers, their socio-emotional developmental outcomes are on the same level or better. Latino children are raised in environments with the ingredients needed to achieve their potential. We use this foundation to propose a strength-based framework for guiding policy investment on Latino children and families.